Collaborative teacher participation in curriculum development : a case study in junior secondary general science (January 1991-November 1991) - Naidoo, Premnandh (Rhodes University, Faculty of Education, Department of Education, 1993)
This research report describes an investigation that involved the collaborative participation of teachers in the redevelopment of parts of the Junior Secondary General Science syllabus. The redevelopment tried to implement environmental education as an innovation. There are two central assumptions that the investigation has made. The first assumption is that the the present Junior Secondary General Science syllabus lacks environmental relevance and therefore the pupils are inadequately prepared to deal with environmental problems. The introduction of a curriculum innovation like environmental education has the potential to bring greater environmental relevance to the syllabus. The second is that such an innovation can be more successfully implemented at schools if it involves the collaborative participation of teachers in the redevelopment of the syllabus. This assumption is made since evidence suggests that curriculum change can be a process of social reconstructive process when it takes place in situ and where teachers and pupils reshape the curriculum in the classroom as the teaching and learning progresses. An action research approach was selected since it is compatible with collaborative teacher, participation in curriculum development. The research design involved three parallel case studies: 1. Clermont Zone, 2. Durban Teachers Centre, 3. Edgewood College. The research confirmed that the Junior Secondary General Science syllabus is perceived by teachers to lack environmental relevance; that teachers, while initially resisting participation in the curriculum development process, were willing to participate if it revolved around their curriculum problems. Significant features of collaborative teacher participation in curriculum development seem to be the co-creation of context by the teachers, the need for institutional support, the production of curriculum materials and the need for networking and intercontextual dialogue. Teachers initially had limited curriculum development skills which needed to be developed. This research process has implications for practical actions 'to enable' the transformation of existing curriculums, and assisting the development of a more democratic and effective education system.
Keywords: Science -- Study and teaching (Secondary) -- South Africa; Curriculum planning -- South Africa; Environmental education -- South Africa